ANALYSIS OF CUSTOMER SATISFACTION WITH LIVIN BY MANDIRI VIRTUAL CREDIT CARD FEATURES - Hartono, Iman Ary; Marleen, Onny; Siregar, Meilani Basaria (Jurnal Techno Nusa Mandiri, 2025)
Credit cards are a payment method that replaces cash, enabling transactions at various locations that accept them. Credit cards can be physical or virtual, with virtual cards facilitating transactions without the need for a physical card. Bank Mandiri offers virtual credit cards to support digital transactions, providing benefits such as discounts and cashback. Although Bank Mandiri experienced a decline in credit card usage during the pandemic, there has been a post-pandemic upward trend influenced by the features of the virtual credit card in Livin' by Mandiri. This is attributed to customer satisfaction, which has become a key factor in this increase. However, as of now, there has been no research conducted on customer satisfaction regarding the virtual credit card feature in Livin' by Mandiri. Therefore, this study aims to analyze customer satisfaction levels with the virtual credit card feature using the PIECES Method (Performance, Information, Economy, Control, Efficiency, and Service). To support the theoretical framework of this issue, relevant journal reviews and data collection through questionnaires were conducted, with the population size based on Bank Mandiri's annual reports for 2022–2023. The analysis of the questionnaire data, employing the PIECES method and the Likert Scale, revealed the highest scores in the categories of Performance and Service, both scoring 4.20. The Efficiency category scored 4.19, while the Information and Control categories each scored 4.15. The lowest score was observed in the Economy category, with a score of 4.13. Therefore, it can be concluded that customers are satisfied.